How Large is the Brain Drain from Italy? - Sascha O. Becker; Andrea Ichino; Giovanni Peri (Center for Economic Studies and ifo Institute (CESifo), 2003)
Using a comprehensive and newly organized dataset the present article shows that the human capital content of emigrants from Italy significantly increased during the 1990's . This is even more dramatically the case if we consider emigrating college graduates, whose share relative to total emigrants quadrupled between 1990 and 1998. As a result, since the mid-1990's the share of college graduates among emigrants from Italy has become larger than that share among residents of Italy. In the late nineties, between 3% and 5% of the new college graduates from Italy was dispersed abroad each year. Some preliminary international comparisons show that the nineties have only worsened a problem of brain drain , that is unique to Italy, while other large economies in the European Union seem to experience a brain exchange . While we do not search for an explanation of this phenomenon, we characterize such an increase in emigration of college graduates as pervasive across age groups and areas of emigration (the North and the South of the country). We also find a tendency during the 1990's towards increasing emigration of young people (below 45) and of people from Northern regions.
Keywords: 330